Conferring authority in the European Union: citizens’ policy priorities for the European Energy Union - Tosun, Jale; Mišić, Mile (Journal of European integration, 2020)
We analyse data from the 2018 Eurobarometer survey to provide a debate on EU authority in the field of energy policy beyond the member states’ preferences. More specifically, we look at why citizens are willing to confer authority to the EU in making energy policy and which policy priorities they indicate. Focusing on public opinion appears promising as the data reveals that European citizens have a more positive stance on allocating policy competences to the EU than the member states’ governments. The descriptive analysis shows that most citizens prefer the Energy Union to prioritise the promotion of renewable energy. This holds particularly true for citizens living in Western Europe that have a left-leaning ideology and who perceive climate change as an issue. For Central-East European citizens, especially those who are right-leaning and perceive energy security as a problem, the Energy Union should give priority to increasing energy security.